PENERAPAN PEMBELAJARAN BERBASIS TEKNOLOGI DALAM MENGEMBANGKAN KETERAMPILAN ABAD 21 - Fauzi Heka Perdana, Farhan; Azhar, Reynaldi; Rizki Musyafa, Helmi; Septiani Rahayu, Galih (Penerbit Lafadz Jaya, 2025)
Amidst the rapid development of technology, schools are expected to be able to utilize digital tools to improve the quality of learning, especially in forming critical, creative, collaborative, and communicative skills in students. This study aims to analyze the application of technology-based learning in developing 21st-century skills at SDIT Islamic Boarding School. This study uses a qualitative case study approach with data collection techniques through observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman analysis model consisting of data reduction, data presentation, and drawing conclusions. The results of the study indicate that technology is integrated into learning using platforms such as Google Classroom, Canva, and YouTube, which support the development of 4C skills. In addition, the findings also reveal the obstacles faced, such as limited infrastructure and variability in students' digital literacy. However, the support of the principal and collaboration between teachers and parental involvement are important factors in overcoming these challenges. The implications of this study are the importance of the role of trained and committed teachers in utilizing technology, as well as the need to develop supporting infrastructure to increase the effectiveness of technology-based learning in Islamic schools.